Спогади і містерія життя Віри Вовк - Гаврилюк, Н. (Слово і Час, 2018)
У статті подано загальну характеристику спогадів В. Вовк “Човен на обрію” та “Місячне
павутиння”. Перші визначено як більш структуровані, з чергуванням біографії та біографічних
нотаток. Біографія сповнена зовнішніми подіями, біографічні нотатки подають духовний життєпис
особи (думки, вражання, емоції). Біографічні нотатки авторки часто тяжіють до притчі, а отже,
постають у контексті новозавітних притч. Притчі передбачають діалог автора-вчителя з читачем-
учнем. Елементи діалогу-повчання містить і містерія. Також у ній зображено духовне життя
персонажів, це наближає містерію до біографічних нотаток. Зовнішніх біографічних подій у
містерії В. Вовк майже нема. Ті, що є, підпорядковані змісту містерії – розкриттю драми спокуси,
гріхопадіння й відкуплення. Вивчається “ Вселенна містерія” В. Вовк і за формальними ознаками.
Встановлено спільні й відмінні риси із середньовічною містерією. The paper provides general description of memories by Vira Vovk named “Boat on the Horizon”
and “Lunar Web”. The first is defined as more structured, with biography and biographical notes
alternating. The biography is full of external events; biographical notes represent the person's
spiritual biography (thoughts, impressions, emotions). The author's biographical notes often tend to
the character of parable, and, therefore, appear in the context of the New Testament parables. The
typical feature of parables is a dialogue between the author-teacher and the reader-student, and the
mystery play contains elements of the dialog instruction as well. The latter also features a spiritual
life of the characters thus being approached to the biographical notes. There are almost no external
biographical events in the ‘mystery play’ of Vira Vovk. The existing ones follow the content of mystery
play, they reveal the drama of temptation, fall and redemption. ‘Universal mystery play’ by Vira Vovk
also can be studied in respect of its formal characteristics. The common and distinctive features with
the medieval mystery have been pointed out.
The division of the mystery play into three parts, that symbolize temptation, the voice of conscience
and restored harmony, is invariable. Therefore the devil appears in the first part of the mystery play,
the devil and the angel fight for the soul in the second, and only the angel appears in the third. There
are three or four acting characters in the drama. The angel and the devil represent all the incorporeal
powers, while the girl and the boy represent all humanity. Nominal quantity of characters is much
larger, which is due to portrayal of the girl and the boy in time perspective and in social roles. В статье представлена общая характеристика
воспоминаний Веры Вовк “Лодка на горизонте” и
“Лунная паутина”. Первые определены как более
структурированные, с чередованием биографии и
биографических заметок. Биография полна внешними
событиями, биографические заметки подают духовное
жизнеописание человека (мысли, впечатления, эмоции).
Биографические заметки автора часто тяготеют к
притче, а следовательно, возникают в контексте
новозаветных притч. Притчи предусматривают диалог
автора-учителя с читателем-учеником. Элементы
диалога-поучения содержит и мистерия. Также в ней
изображена духовная жизнь персонажей, что приближает
мистерию к биографическим заметкам. Внешних
биографических событий в мистерии В. Вовк почти нет. Те,
что есть, подчинены содержанию мистерии – раскрытию
драмы искушения, грехопадения и искупления. Изучается
“Вселенная мистерия” В. Волк и по формальным
признакам. Установлено сходства и различия со
средневековой мистерией.